OLD AGE, QUALITY OF LIFE AND RELATIONSHIPS IN A COMMUNITY- BASED NURSING HOME (Fiep Bulletin - online, 2011)
The present article, is part of a research initiated in the year of 2006 in the Institution to put in a home Vila Vicentina Júlia Freire in João Pessoa - Paraíba, who has for objective, to observe the behavior of lodged in relation its personal life, socialization and way of life, being aimed at its corporal image. The lodged ones of Vila have its values based on the individual experience of each one. To value the corporal image arrives to be an almost instinctive attitude, in view of the care that the women and the men have with its appearance and the concern with what the others think. The experience in the Village has presented the relationships between the aged ones, and the way of them to face its sexuality and forms of relationship enters its pairs bringing á tona of this form the same conflicts that we find in the society it are of the shelter. The aged ones keep social relations, exactly liveing in separate rooms, where it keeps a social life in the collective environments that serve of a great square of socialization and collective life.
Keywords: vieillesse; qualité de vie; relations